ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK MASA COVID-19 KELAS V SD NEGERI 03 PONTIANAK SELATAN - Fikri Ananda; Hery Kresnadi; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
ABSTRACTThis study aims to describe the completeness and suitability of the components of the thematic learning implementation plan during the Covid-19 pandemic by referring to circular letter from Ministry of Education and Culture Number 14 in 2019 about the simplification of the Learning Implementation Plan. The research method used is a descriptive method with a qualitative research form. The source of the data for this research is a teacher in the fifth grade of Elementary School 03, South Pontianak. The data of this research are in the form of a thematic learning implementation plan document as well as the results of the interview process of the preparation of the lesson plan with the teacher in the fifth grade of Elementary School 03, South Pontianak. The results of the analysis show that the completeness and suitability of the components of the learning implementation plan made by the teacher is not fully complete and in accordance with the circular letter from Ministry of Education and Culture Number 14 in 2019.Keywords :AnalysisImplementation PlanThematic learningCovid-19